Development of a Malaysian Sign Language Interpreter by using Image Recognition Techniques for the Community to Understand the Deaf - Mohammad, Nurul Ashikin; Kian Sek, Tee (Evolution in Electrical and Electronic Engineering, 2021)
In Malaysia, people with hearing problems still suffer going through their daily life because they struggle to have a conversation with the community who does not know or how to do sign language efficiently. This project aims to develop a Malaysian Sign Language interpreter to convert hand sign language to texts, in order to facilitate the conversation between the deaf and the community. Basically, when a hand sign is detected by the camera device, a text will be shown to its corresponding meaning. The requirement for this project is a laptop or desktop that has camera access for image recognition and internet access to connect to Jupyter Notebook to run the specific coding. The system would implement a camera and vision system to capture images of hand signs. These images would be further been annotated correlated to their meaning. It will undergo a training process digitally and eventually being digitally recognized using a series of image processing algorithms and recognition algorithms. Lastly, the system will detect hand signs and interpret the meaning of the hand sign by using the camera. Hence, the community can understand them well and able to communicate. At the end of this project, the system able to convert hand sign into visible text and manage to help the deaf to connect to community in their daily life.